Factors Influencing the Investment Decisions of the Salaried Class in Pakistan The Roles of Saving Behavior, Consumption Patterns, Retirement Planning, and Living Standards - Waqar Munir, Munir (University of Malaysia Sarawak Campus, 2024)
According to the theories of development economics and behavioural economics, saving is important for economic growth. Life-cycle and permanent income hypotheses are important for private saving behaviour and investment. The data was collected in person or by email, using quota sampling of 459 salaried people with modified and adapted questionnaires for quantitative analysis from federal employees on scales from BPS-17 to BPS-22. The study's unique quantitative framework addresses private saving, consumption, and retirement planning with financial investment decisions. Smart-PLS v3.0 and SPSS v25.0 were used for regression analysis and the instrument's reliability and validity. The PLS-SEM results revealed that living standards do not affect saving and investment as much as consumption and investment in moderation. A strong relationship existed between saving, consumption, living standards, retirement planning, and investment decisions. Investment scams affect retirement planning, saving, and investment decisions. The moderation of retirement planning showed no effect on scams and investment decisions, as well as between consumption and investment decisions. The chi-square test showed that demographics positively affected savings and investment decisions, except for pay scale and profession. There is a need for better policies, regulations, and benefits to manage investment fraud and help employees with retirement planning. Policymakers and the government should encourage saving to boost economic growth and capital inflow, benefiting individuals, the government, and society as a whole.